Learning English Grammar by Means of M-Learning: A Case Study - Bilotserkovets, Marina; Fomenko, Tatiana (Educational Challenges, 2022)
Purpose. The paper deals with the effective implementation of mobile applications for learning grammar in the EFL course for students of non-linguistic higher educational institutions. The tasks for the research are the following: to discover the didactic properties of mobile applications that enable students’ progress in learning English grammar and to apply them; observe students’ attitudes towards mobile learning applications for training English grammar skills and their grounds. Methodology. Quantitative outcomes of the experiment were calculated by means of the knowledge ratio technique. Scaling method was applied to organize the data into numerical form for comparative analysis of the experimental groups and control groups’ achievements. A case study was conducted on the basis of Sumy National Agrarian University, Ukraine. A sample consisted of two experimental groups (35 students), and two control groups (36 students), aged 18-19, who studied second year at different faculties during 2021-2022 in the University and participated voluntarily in the study. In experimental groups the studying process was organized with the implementation of tablets and cellphones with the ability to access the Internet via Wi-Fi as mobile learning tools and mobile learning applications. A series of the interviews were held to learn students’ attitudes towards mobile apps. Results. English grammar command levels in experimental groups are predominantly sufficient and high in contrast to the predominantly low and initial levels in control groups. The attitudes of students towards mobile apps for learning EFL are mostly positive. Conclusions. It was concluded that the implementation of mobile learning tools provided the efficient mastering of English grammar by students of non-linguistic higher educational institutions. Improving of EFL teachers’ methodological preparation for the introduction of mobile learning requires further researches in this sphere.